DAMPAK MEDIA SOSIAL TIKTOK TERHADAP INTERAKSI SOSIAL SISWA SMP 4 TAROGONG KIDUL - Marwa Rizki Nur Muhamad; Triani Widyanti; Hendro Sugiarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
TikTok has become one of the most widely used social media platforms among adolescents, including junior high school students. The use of TikTok is not only limited to entertainment but also serves as a medium for communication, information seeking, and self-expression. This study aims to understand and describe the impact of TikTok social media usage on the social interactions of students at SMP 4 TarogongKidul. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that TikTok has become an integral part of students' daily lives and is utilized for obtaining information, entertainment, and maintaining communication with peers. The use of TikTok provides positive impacts, such as facilitating communication, expanding social networks, enhancing creativity, and increasing self-confidence in self-expression. However, excessive use of TikTok also leads to negative impacts, including reduced face-to-face interactions, increased dependence on social media, and shifts in communication patterns from direct interaction to digital communication. Therefore, TikTok should be used wisely to maximize its benefits while maintaining the quality of students' social interactions.